Rhodium-catalyzed C–H functionalization of heteroarenes using indoleBX hypervalent iodine reagents - Grenet, Erwann; Das, Ashis; Caramenti, Paola; Waser, Jérôme (Beilstein Journal of Organic Chemistry, 2018)
The C–H indolation of heteroarenes was realized using the benziodoxolone hypervalent iodine reagents indoleBXs. Functionalization of the C–H bond in bipyridinones and quinoline N-oxides catalyzed by a rhodium complex allowed to incorporate indole rings into aza-heteroaromatic compounds. These new transformations displayed complete regioselectivity for the C-6 position of bipyridinones and the C-8 position of quinoline N-oxides and tolerated a broad range of functionalities, such as halogens, ethers, or trifluoromethyl groups.
Keywords: C–H activation; hypervalent iodine; indoleBX; indoles; pyridinones; rhodium catalysis